The effect of FDI towards GDP growth in Malaysia / Tismazammi Mustafa ... [et al.] - Mustafa, Tismazammi; Nik Hassan, Nik Suriati; Mohd Hassan, Norsilawati; Mohd Isyak @ Zainudin, Fadhilah (2021)
Foreign direct investment (FDI) has been an important source of GDP growth for Malaysia, bringing in capital investment, technology and management knowledge needed for economic growth. The aim of this research is to investigate the effect of foreign direct investment towards economic growth in Malaysia. The time series data, Ordinary least square (OLS) regressions and the empirical analysis were conducted by using annual data on FDI and GDP in Malaysia over the period of 1989 to 2018. This paper used annual data from IMF International Financial Statistics tables, published by International Monetary Fund to find out the relationship between FDI and economic growth in Malaysia. The results show that GDP, foreign direct investment, inflation and export series in Malaysia are I(1) series. FDI has a direct positive effect on GDP. Furthermore, other control variables inflation and export have different sign of impact on GDP